2014
DOI: 10.31055/1851.2372.v49.n4.9891
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización morfológica y molecular de las variedades locales de frijol común cultivado en el altiplano mexicano semi-árido.

Abstract: Caracterización morfológica y molecular de las variedades locales de frijol común cultivado enel altiplano mexicano semi-árido. El objetivo de este trabajo fue caracterizar el frijol común de parcelasagrícolas cultivadas con variedades criollas de frijol común de la región semiárida del altiplano mexicanoutilizando datos morfológicos y de Polimorfismos en la Longitud de los Fragmentos Amplificados (AFLPs). Las características morfológicas fueron discriminantes y mostraron la agrupación de las 150 accesiones en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The frequency of "dark red" seed was maximum (40%) followed by "red", "white" and "brown" with the frequency of (30%) (15%) and (15%) respectively. Papa and Gepts, (2003) and Langarica et al (2014) inferred that purple and pink flowers confer black seed coats.…”
Section: Largementioning
confidence: 99%
“…The frequency of "dark red" seed was maximum (40%) followed by "red", "white" and "brown" with the frequency of (30%) (15%) and (15%) respectively. Papa and Gepts, (2003) and Langarica et al (2014) inferred that purple and pink flowers confer black seed coats.…”
Section: Largementioning
confidence: 99%
“…Purseglove [1] and Singh et al [15] reported a wide variability in growth habit in French bean. Garcia et al [28], Rosales-Serna et al [29] and Langarica et al [30] demonstrated that indeterminate growth habit with climbing ability and extend physiological maturity leads to more productive than plants with determinate growth habit. Rosales-Serna et al [29]; Beebe et al [31]; Langarica et al [30] found significant diversity for growth habit in French bean genotypes.…”
Section: Growth Habitmentioning
confidence: 99%
“…Garcia et al [28], Rosales-Serna et al [29] and Langarica et al [30] demonstrated that indeterminate growth habit with climbing ability and extend physiological maturity leads to more productive than plants with determinate growth habit. Rosales-Serna et al [29]; Beebe et al [31]; Langarica et al [30] found significant diversity for growth habit in French bean genotypes. Garcia et al [28] and Langarica et al [30] reported predominant presence of indeterminate, with nonclimbing shoots in French bean genotypes.…”
Section: Growth Habitmentioning
confidence: 99%
See 2 more Smart Citations